Dyspnea on swallowing: a case of thyroid lymphoma (Bangladesh Journal of Medical Science, 2017)
Purpose: The main sign of osteoporosis is a significant decrease of bone mass that is caused by imbalance between resorption and osteogenesis. There are two main factors that contribute to the genesis of this illness. All these factors bring todecrease of thickness of bone and its destruction doesnt depend on their combination. Therefore, our objective was to study the changes in the alveolar bones of elderly people in secondary edentulous.Material and Methods: For deeper study of morphological changes in segments of teeth we have conducted pathological researches of biopsy material of dead patients at the Center of Pathological Studies of the Sumy Medical University. The first group of patients included n=7 who died of various somatic abnormalities and had no significant atherosclerotic lesions. The second group includes segments of teeth and jaws of patients n=7 who died from complications of atherosclerosis In our studies, we used: Histological study; Fluorescence microscopy; Immunohistochemistry; Microphotography and image analysis; Mathematical calculations.Results: Based on the statistical analysis we can see a downward trend in the number of osteocytes in trabeculae of the periapical third part of the tooth at atherosclerosis 26.85±7.44; P=0.05. We can also see the dependence of trabecular thinning of toothless area of the alveolar bone 226.57±70.53; P=0.02 from losing of teeth against the background of atherosclerosis with hypertension. The osteopontin expression and fluorescencetion of toothless bone area also tend to decrease in atherosclerosis and hypertension 42.81±16.24; P=0.048.Conclusion: The cause of tooth loss is difficult to determine, since it is not clear whether it is due to osteoporosis or some forms of periodontitis in patients. The bone resorption has actived by reactive oxygen species both during atherosclerosis. Through our research found out that in order to reduce changes in the toothless bone we should reduce the pressure on chewing toothless alveolar sprout by dental implants.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.138-141